Winter outdoor thermal comfort of older people with different degrees of frailty: A study in Nanyang city, China’s hot-summer and cold-winter region - Dong Yan; Peng Zhang; Zhiyuan Liu; Ran Chen; Biao Wang (PLoS ONE, 2026)
The thermal comfort of outdoor environments in winter directly impacts the spatial utilization efficiency of urban parks and the physical and mental health of the elderly. This study uses Nanyang People’s Park, which is popular for local elderly, as a case study. Using the FRAIL scale to categorize different levels of frailty, combined with objective microclimate field measurements and subjective thermal comfort questionnaires, the study conducts regression analysis between the calculated physiological equivalent temperature and the thermal comfort voting results. A model for evaluating the thermal comfort of older people in urban parks during winter in hot summer and cold winter regions (HSCW) is established. The study also explores the relationships between physical, personal, social, and psychological factors and the outdoor thermal comfort of the elderly, as well as the differences in thermal adaptation among older people with varying degrees of frailty. The research findings show that the neutral temperature for no frailty is 10.29°C, 9.60°C for pre-frailty, and 8.65°C for severe frailty. As the degree of frailty increases, the outdoor thermal sensitivity of the older people gradually weakens. The adaptive behaviors of older people with different levels of frailty are greatly influenced by their specific environment. The research results provide basic data reference for the design of aging-friendly urban parks in HSCW, and also provide a renovation reference for relevant government departments to formulate the thermal comfort standards of urban parks.